PERANCANGAN IDENTITAS VISUAL PRODUK TEH HERBAL BUNGA TELANG UNTUK MENINGKATKAN DAYA TARIK KONSUMEN DI DESA CIKELAT - Novia, Irsa; Hidayat, Alfiansyah; Ahmad Gozali, Rizqi; Alamsyah, Zaenal (Jurnal Abdi Nusa, 2025)
Telang Flower Herbal Tea is a herbal drink produced from butterfly pea flowers (Clitoria ternatea), a plant that grows abundantly in tropical areas, including Indonesia. Butterfly pea flower, also known as butterfly pea flower or blue flower, has a distinctive blue color that gives this herbal tea its color and natural properties. This research is the result of collaboration between Nusa Putra Sukabumi University and Cikelat Village, in an effort to increase the attractiveness of telang flower herbal tea products. The product's visual identity is the main focus of this research, with the aim of creating a strong and attractive visual identity to increase consumer appeal. A strong visual identity can help these products be more easily recognized by consumers, create a positive image, and increase confidence in the product's quality. Visual identity design involves color selection, logo design, packaging design, and branding strategy, as well as active participation from the Cikelat Village community to ensure conformity with local values and culture. It is hoped that this research will provide benefits to the people of Cikelat Village, enrich students' educational experiences, and become a reference for other rural communities who are trying to increase the competitiveness of local products through designing effective visual identities.Keywords: Telang Flower, Visual Identity, Cikelat Village